Processing on the physical and physiological quality of seeds of Guinea grass - Melo, Lilian Faria de [UNESP]; Martins, Cibele Chalita [UNESP]; Silva, Givanildo Zildo da [UNESP]; Brandao Boneti, Joao Eduardo [UNESP]; Vieira, Roberval Daiton [UNESP] (Univ Federal Ceara, Dept Geol, 2016)
Seeds received by forage-grass companies after harvesting contain impurities which are removed by processing machines. This procedure is necessary to obtain seeds which are within the standards of quality for marketing and sowing. The aim of this work was to evaluate the effects of the processing stages on the physical and physiological quality of seeds of guinea grass cv. Mombasa (Panicum maximum), with a view to marketing. Seeds were sampled before processing and after leaving the air screen machine (output from the upper, intermediate and bottom screens), first gravity table (drift, upper and intermediate output), treating machine, and second gravity table (upper, intermediate, and lower output). The seeds were evaluated for water content, physical quality (purity and thousand-seed weight) and physiological quality (germination, first count, classification of seedling vigour, accelerated ageing, seedling length, seedling emergence in the field, and speed of emergence index). Seed processing in the air and screen machine and the gravity table is efficient in improving the physical and physiological quality of the lots of P. maximum cv. Mombasa seed. For this species, processing is necessary to meet the demands for purity and germination established by the Brazilian standards for seed marketing.
Keywords: Panicum maximum; Germination; Vigour; Processing; Purity; Forrage grasses